2014
DOI: 10.1016/j.neuron.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Triad3A Regulates Synaptic Strength by Ubiquitination of Arc

Abstract: Summary Activity-dependent gene transcription and protein synthesis underlie many forms of learning-related synaptic plasticity. At excitatory glutamatergic synapses, the immediate early gene product Arc/Arg3.1 couples synaptic activity to postsynaptic endocytosis of AMPA-type glutamate receptors. Although the mechanisms for Arc induction have been described, little is known regarding the molecular machinery that terminates Arc function. Here we demonstrate that the RING domain ubiquitin ligase Triad3A/RNF216 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
190
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(203 citation statements)
references
References 50 publications
12
190
1
Order By: Relevance
“…S1). This protein degradation pathway is mainly mediated via the ubiquitin-proteasome system (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…S1). This protein degradation pathway is mainly mediated via the ubiquitin-proteasome system (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…All constructs were verified by sequencing. HA-tagged ubiquitin, pGL3-BAR, TK-Renilla, pHAGE β-catenin WT, and pHAGE β-catenin mutant constructs were were previously described (39,66,67). G76V-Ubiquitin-GFP was obtained from Addgene (23969).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, numerous neuronal E3s have been identified that functionally regulate specific levels of postsynaptic proteins. These include γ-actin (79), GKAP, and Shank (80), which are regulated by TRIM3, PSD95 by Mdm2 (13) upon facilitation by CDK5 (81), AMPARs by RNF167 (82), and the postsynaptic cytoskeletal protein and immediate early gene Arc by both UBE3A (83) and RNF216/TRIAD3 (84). Targeted ubiquitination of presynaptic proteins is also prominent.…”
Section: Discussionmentioning
confidence: 99%